Overcoming challenges in earthquake preparedness in Panay Island in the Philippines through good governance - Atando, Ramil B. (2018)
Disaster risk reduction is a major concern especially among developing and underdeveloped countries. This case study reviewed the governance strategies in place to manage the potential impacts of a magnitude 7.0 earthquake in Panay Island, which is home to more than 2 million inhabitants. National and local government offices engaged in disaster management provided the secondary data needed for this case study. Key informant interviews were conducted to collect salient information on governance strategies employed to enhance the analysis and credibility of this research. Among the key findings..
Keywords: Earthquakes; Earthquake preparedness and challenges